Three-dimensional finite element analysis of the stress distribution pattern in a mandibular first molar tooth restored with five different restorative materials - Kathleen Manuela D'souza; Meena Ajay Aras (Wolters Kluwer Medknow Publications, 2017)
Introduction: Badly broken or structurally compromised posterior teeth are frequently associated with crown/root fracture. Numerous restorative materials have been used to fabricate indirect full-coverage restorations for such teeth. This study aims to evaluate and compare the effect of restorative materials on the stress distribution pattern in a mandibular first molar tooth, under varying loading conditions and to compare the stress distribution pattern in five commonly used indirect restorative materials. Materials and Methods: Five three-dimensional finite element models representing a mandibular first molar tooth restored with crowns of gold, porcelain fused to metal, composite (Artglass), alumina-based zirconia (In-Ceram Zirconia [ICZ]), and double-layered zirconia-based materials (zirconia core veneered with porcelain, Lava) were constructed, using a Finite Element Analysis Software (ANSYS version 10; ANSYS Inc., Canonsburg, PA, USA). Two loading conditions were applied, simulating maximum bite force of 600 N axially and normal masticatory bite force of 225 N axially and nonaxially. Results: Both all-ceramic crowns allowed the least amount of stress distribution to the surrounding tooth structure. In maximum bite force-simulation test, alumina-based all-ceramic crown displayed the highest von Mises stresses (123.745 MPa). In the masticatory bite force-simulation test, both all-ceramic crowns (122.503-133.13 MPa) displayed the highest von Mises stresses. Conclusions: ICZ crown displayed the highest peak von Mises stress values under maximum and masticatory bite forces. ICZ and Lava crowns also allowed the least amount of stress distribution to the surrounding tooth structure, which is indicative of a favorable response of the underlying tooth structure to the overlying full-coverage indirect restorative material. These results suggest that ICZ and Lava crowns can be recommended for clinical use in cases of badly damaged teeth.